98.4k views
4 votes
Solve the equation. − 3 ( 3 − 4 x ) = 5 ( x − 1 ) + 7 ( x + 2 ) Show each step you used to solve the equation. Determine whether the equation has one solution, no solution, or infinitely many solutions. Explain your reasoning.

1 Answer

5 votes

Answer:

0=18

Explanation:

-3(3 - 4x) = 5(x - 1) + 7(x + 2)

-3( -4x + 3) = 5(x - 1) + 7(x + 2)

User Fernando Morales
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.